A Systematic Review of NT-proBNP as Prognostic Biomarker for Preeclampsia Complications - Bachnas, Muhammad Adrianes; Asaduddin, Aiman Hilmi; Ali, Agni Shalha; Indarta, Ardhia Fefrine; Anshari, Shafira Yasmine; Febrinasari, Ratih Puspita; Widyaningsih, Vitri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Preeclampsia can lead to maternal and fetal complications due to its ability to cause multiple organ disorders. Interestingly, N-terminal pro-brain-type natriuretic peptide (NT-proBNP) levels were higher in preeclampsia than in non-preeclampsia, representing cardiovascular mal¬function as the potential cause. Moreover, NT-proBNP also has a potential role in predicting complications that will arise in preeclampsia. This systematic review was performed to determine the role of NT-proBNP plasma levels in predicting maternal and fetal complications in preeclampsia.Subjects and Method: This systematic review was conducted based on PRISMA-P by previous observational study from scientific databases, namely Hinari, Cochrane Library, ScienceDirect, Scopus, and grey literature in OCLC’s OAISTER between 2006 and 2021. The search keyword used were ((NTproBNP) OR (NT-proBNP) OR (N-terminal pro-BNP) OR (N-terminal pro-Brain Natriuretic Peptide)) AND ((preeclampsia) OR (pre-eclampsia)) AND (pregnancy complications). Newcastle - Ottawa Quality Assessment Scale (NOS) was used to assess quality of included studies.Results: After study selection, five studies from 156 studies were considered eligible and selected in this systematic review. The results showed that pre-eclampsia complications occurred with NT-proBNP levels above 500 mg/dL, which cardiovascular complications may occurred above 700 mg/dL. NT-proBNP levels were higher in women with maternal complications such as placental abruption, HELLP (Hemolysis, elevated liver enzyme levels, and low platelet levels) syndrome, eclampsia, pulmonary oedema, congestive heart failure, cerebrovascular accident, renal dysfunction, and hypertensive retinopathy. Furthermore, increased NT-proBNP levels were associated with fetal growth restriction, resulting in low birth weight. NT-proBNP was significantly higher in pregnant women due to a combination of pre-existing volume overload and NT-proBNP clearance dysfunction in kidney. Conclusion: NT-proBNP levels were associated with adverse outcomes in preeclampsia. NT-proBNP serum levels could be used to predict maternal-fetal complications in preeclampsia.